Evaluation of residential satisfaction of low-cost housing in Kano state - Sapian, Abdul Razak; Denan, Zuraini; Nour, Nabilah (IIUM Press, 2008)
Hausa vernacular houses before the colonial period have satisfied the needs and socio-cultural requirements of their occupants. However, low-cost housing design nowadays is detached from the needs of its users. This paper assessed the level of residential satisfaction of low-cost housing respondents based on six socio-cultural values inherent in Hausa vernacular. The survey method was used to investigate and determine the respondents' perception on the socio-cultural performance of these low-cost housing. A total of 360 questionnaires were administered to low-cost housing respondents in Kana via snowball sampling. The findings show that the satisfaction indexes of 50% of the respondents fall within the medium region and that the majority of them consider it very important for socio-cultural values to be integrated in the design of their residences. The findings suggest that a greater consideration should be paid to the people's preferences and their socio-cultural needs when designing public housing.